MARKETING STRATEGIES ON KOSPITAL BY KHAS BENGKULU (Case Study: Kiosk By By Fajri, Taste, Sari Rasa) - Novia Triana Yasiruddin; Suwarni; Ida Ayu Made Er Meytha (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
The purpose of the study was to find out how the marketing strategy of the Kios By By Fajri business, Sari Rasa and Taste of Bengkulu City. This type of research is descriptive research with qualitative methods, namely identifying internal strengths, weaknesses and identifying external opportunities and threats faced by the Kiosk business by By Fajri, Sari Rasa and Taste in marketing products, in order to obtain the most appropriate strategy that can be used in the future. which will come. Methods of data collection using a questionnaire with a sample of 84 respondents Incidental Sampling technique with SWOT analysis method. From the results of the IFAS and EFAS calculation research, there are strengths in the Fajri kiosk business in Bengkulu City of 1.88 while the weakness is 0.93, the Sari Rasa kiosk has a strength of 2.19 and a weakness of 0.67, and Cita Rasa has a strength of 1, 96, so the internal factor cell (quadrant) is Fajri's kiosk, which is 1.88 – 0.93 = 0.95, Sari Rasa has an internal factor of 2.19 – 0.67 = 1.52 and Taste has an internal factor of 1.96 – 0 ,67 = 1.29 while the opportunity owned by Fajri's kiosk is 1.29 with a threat of 1.14, while Sari Rasa has an opportunity of 1.38 and a threat of 1.29, and Rasa Rasa has an opportunity of 1.66 and a threat of 1, 10, so the external cell (quadrant) factor is Fajri kiosk which is 1.29 – 1.14 = 0.15, while the Sari Rasa kiosk is 1.38 – 1.29 = 0.09 and Taste is 1.66 – 1, 10 = 0.56 so that the Fajri, Sari Rasa and Rasa Rasa kiosks are in cell (quadrant) I in the SWOT analysis diagram.